Teknik Radiografi Os Humerus dengan Kasus Fraktur 1/3 Distal Humerus di Instalasi Radiologi Rumah Sakit Efarina Etaham Berastagi Kabupaten Karo - Taslima, Saufa; Simanjuntak, Zilvayani (3031-8572, 2022)
Humerus fracture is a disruption of the continuity of the humerus bone accompanied by soft tissue damage. Radiographic examination is essential for documenting and determining the extent of fractures. This study aims to determine the radiological examination procedures for humerus fractures and radiation protection efforts at the Radiology Installation of Efarina Etaham Hospital, Berastagi, Karo Regency. This is a qualitative descriptive study using secondary data collection methods through observation, physical examination, and documentation study. The subject was a 37-year-old male patient with a diagnosis of 1/3 distal humerus fracture. Radiographic examination was performed using AP (Anteroposterior) projection with exposure factors of 65 kVp, 160 mA, and 0.6 seconds, using a 24x30 cm cassette at 100 cm FFD. The results showed that the PA projection effectively visualized the fracture while providing patient comfort and reducing the risk of aggravating the injury. However, radiation protection for patients was not optimal as protective aprons could not be used to avoid interfering with the radiographic image. It is concluded that the radiographic technique applied can produce optimal diagnostic images, but radiation protection aspects need improvement, especially regarding the use of collimation and proper field size management